Barriers and Facilitators in the Clinical Implementation of Beta-Lactam Therapeutic Drug Monitoring in Critically Ill Patients: A Critical Review. Issue 1 (February 2022) - Abdulla, Alan; van den Broek, Puck; Ewoldt, Tim M. J.; Muller, Anouk E.; Endeman, Henrik; Koch, Birgit C. P.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: With increasing knowledge of beta-lactam pharmacodynamics and interpatient and intrapatient variability in pharmacokinetics, the usefulness of therapeutic drug monitoring (TDM) is becoming increasingly clear. However, little research has been conducted to identify potential barriers and facilitators in the clinical implementation of beta-lactam TDM. This study provides an overview of the current practices of beta-lactam TDM and barriers and facilitators in its implementation. Methods: A systematic search was conducted using the Ovid MEDLINE database in April 2021, without restrictions on the publication date. All studies reporting the implementation of beta-lactam antibiotic TDM in critically ill patients through questionnaires or surveys were included in this review. Results: Six eligible studies were identified from 215 records, all of which were cross-sectional. All studies identified barriers and facilitators in the implementation of beta-lactam TDM in critically ill patients. The main barriers were insufficient knowledge about various aspects regarding the implementation of beta-lactam TDM and the unavailability of assays. Furthermore, a delay in the acquisition of TDM results reduces the probability of physicians altering drug dosages. Finally, doubts about the cost-effectiveness and clinical effectiveness of beta-lactam TDM in critically ill patients hinder broad implementation. Moreover, to improve the willingness of physicians to use beta-lactam TDM, collaboration between physicians and clinical pharmacists and clinical microbiologists should be strengthened. Conclusions: Although the evidence for application of beta-lactam TDM continues to grow, its clinical implementation remains limited. To enable optimal implementation of these antibiotics in critically ill patients, several barriers need to be overcome regarding logistics, equipment availability, clinical evidence, and proof of cost-effectiveness.